Menumbuhkan Jiwa Enterpreneurship Mahasiswa STT Real Batam Melalui Kegiatan PKM Tahu Tempe Sebagai Jembatan Pewartaaan Injil - Fredy Simanjuntak; Mangiring Tua Togatorop; Ardianto Lahagu; Roy Martin Simanjuntak; Stefanus Meo Nekin (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2020)
This article discusses the Creativity Program initiated by the Theology Study Program with STT Real Batam students to take advantage of their free time to cultivate the entrepreneurial spirit of students through the skills of making tofu and tempeh. This was initially motivated by daily needs in the dormitory so that students could also eat simple, everyday foods that are no less healthy and beneficial for the body. The implementation method for this PkM program is by visiting one of the tofu-tempe production centres in Batu Aji. The purpose of the activity is to provide skills to students so as to foster an entrepreneurial spirit for STT Real Batam students. From the results of the evaluation, it was noted that he had attended several pieces of training from theory to practice. Students are motivated to develop such training in the campus environment. The implementation of this PKM is very useful to increase student creativity so that the production of tofu and tempeh can be used as a medium for Micro, small and medium enterprises and at the same time to complement the daily food needs of the hostel.AbstrakArtikel ini membahas tentang Program Kreativitas yang digagas oleh Prodi Teologi dengan mahasiswa STT Real Batam untuk memanfaatkan masa luang untuk menumbuhkan jiwa enterpreneuship mahasiswa melalui keterampilan pembuatan tahu dan tempe. Hal ini awalnya dimotivasi kebutuhan sehari-hari di asrama supaya mahasiswa pun dapat mengkomsi makanan sederhana sehari-hari yang tak kalah sehat dan bermanfaat bagi tubuh. Metode pelaksanaan pada program PkM ini yaitu dengan mengunjungi salah satu pusat produksi tahu-tempe di Batu Aji. Tujuan kegiatan adalah untuk memberikan meningkatkan keterampilan kepada mahasiswa sehingga menumbuhkan jiwa enterpreneurship bagi mahasiswa STT Real Batam. Dari hasil evaluasi, tercatat selama mengikuti beberapa kali pelatihan dari teori sampai praktek. Mahasiswa termotivasi untuk mengembangkan pelatihan pembuatan tersebut di lingkungan kampus. Pelaksanaan PKM ini sangat berguna untuk meningkatkan kreativitas mahasiswa untuk ditambah hasil produksi tahu dan tempe dapat dijadikan sarana UMKM dan sekaligus untu melengkapi keperluan makanan asrama sehari-hari.